Peran Mediasi Kepuasan Kerja Pada Pengaruh Kompensasi Dan Beban Kerja Terhadap Kinerja Karyawan Di Satuan Latihan Brigade Mobile (Brimob) - Dewi, Riski Fitria; Julianti, Emma; Ronny, Ronny (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
The aim of this research is to analyze the direct influence of compensation, workload, job satisfaction on employee performance. Also analyzes the indirect effect of compensation and workload on employee performance through the mediation of job satisfaction. The sampling technique used purposive sampling with 176 respondents of Mobile Brigade Training Unit (Brimob) personnel. The analysis technique used is PLS-SEM. The results show that compensation had a positive affect on personel performance, compensation does not affect on job satisfaction, workload does not affect on personel performance, workload has a negative affect on job satisfaction, compensation has a positive affect on job satisfaction. Job satisfaction is able to mediate compensation on personel performance, but job satisfaction is not able to mediate workload on employee performance. Keywords: Workload, Employee Performance, Job Satisfaction, Compensation